1996
DOI: 10.1017/s0033291700033687
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological and structural brain changes in anorexia nervosa before and after refeeding

Abstract: SynopsisThe neuropsychological performance and Magnetic Resonance Imaging (MRI) brain appearance of a consecutive series of 46 in-patients with anorexia nervosa (AN) was compared with hat of 41 normal-weight controls. The groups were matched for sex, age, estimated pre-morbid intelligence and education. AN patients who had gained at least 10% of their body weight were retested and rescanned. Controls were retested after a similar interval. The AN group performed significantly worse than the controls on tasks m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
203
8
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(235 citation statements)
references
References 24 publications
20
203
8
4
Order By: Relevance
“…While more speculative, it is possible that other symptoms, such as diminished insight and motivation to change, and altered central coherence, could be related to disturbed interoceptive awareness. Those with AN fail to accurately recognize and incorporate affective and social stimuli in the environment, as confirmed by laboratory tests (19,20). Furthermore, individuals with AN have enhanced ability to pay attention to detail or use a logical/analytic approach, but exhibit worse performance with global strategies (19,22).…”
Section: The Insula and Interoceptive Awarenessmentioning
confidence: 95%
See 1 more Smart Citation
“…While more speculative, it is possible that other symptoms, such as diminished insight and motivation to change, and altered central coherence, could be related to disturbed interoceptive awareness. Those with AN fail to accurately recognize and incorporate affective and social stimuli in the environment, as confirmed by laboratory tests (19,20). Furthermore, individuals with AN have enhanced ability to pay attention to detail or use a logical/analytic approach, but exhibit worse performance with global strategies (19,22).…”
Section: The Insula and Interoceptive Awarenessmentioning
confidence: 95%
“…For example, they often feel that they should be able to do things perfectly without making mistakes, and they have little appreciation for the fact that mistakes are a normal learning experience. Moreover, they often fail to accurately recognize and incorporate affective and social stimuli in the environment, as confirmed by laboratory tests (19,20). Those ill with and REC from (REC) AN tend (21) to have delayed setshifting, which allows for the adaptation of behavior in line with changing demands of the environment.…”
Section: Neurocognitionmentioning
confidence: 99%
“…Findings in clinical populations are inconsistent and limited by small, diagnostically diverse groups and the use of variable outcome measures. [1][2][3] Although most neuropsychological studies in anorexia nervosa (AN) have suggested impairments in higher-level executive, memory, learning, and visuospatial functioning, [3][4][5][6][7][8][9][10][11][12][13] some have not found abnormalities [14][15][16] and others have found superior functioning. [17][18] Some of these studies have lacked a normal control group (NC) 7,12 thereby limiting these findings.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18] Some of these studies have lacked a normal control group (NC) 7,12 thereby limiting these findings. Cognitive deficits in AN may be the consequence of factors other than nutritional deficiency, 1 as a number of studies have neither demonstrated amelioration following nutritional restoration [4][5][6][19][20][21][22] nor correlation with low body mass indices (BMI). 7,23 Although the remission of physical symptoms in AN generally precedes psychological recovery, 24 findings regarding the effect of weight-recovery on neuropsychological function in AN have been conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the role of neurobiology of AN has become increasingly important for understanding the etiology and complications of the condition. Structural brain changes have been identified in low weight patients with AN, and include reduced brain volume in both gray and white matter structures and enlarged lateral ventricles (Boghi et al, 2011;Castro-Fornieles et al, 2009;Golden et al, 1996;Hoffman et al, 1989;Katzman et al, 1996Katzman et al, , 1997Kingston et al, 1996;Muhlau et al, 2007;Roberto et al, 2011;Swayze et al, 1996Swayze et al, , 2003. While the etiology of these changes has not yet been elucidated, decreased brain volumes observed in AN may, in part, reflect reductions in white matter volume that occur secondary to reductions in myelin content from the effects of malnutrition (Swayze et al, 2003).…”
Section: Introductionmentioning
confidence: 99%